2018
DOI: 10.1039/c7ta08251g
|View full text |Cite
|
Sign up to set email alerts
|

Triazine-based conjugated microporous polymers with N,N,N′,N′-tetraphenyl-1,4-phenylenediamine, 1,3,5-tris(diphenylamino)benzene and 1,3,5-tris[(3-methylphenyl)-phenylamino]benzene as the core for high iodine capture and fluorescence sensing of o-nitrophenol

Abstract: A series of novel triazine-based conjugated microporous polymers were constructed via Friedel–Crafts polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 70 publications
2
97
0
3
Order By: Relevance
“…reported synthesis of CMPNs via olefin metathesis reaction using trifunctional styrene derivatives and studied its fluorescence quenching behavior for the detection of RDX at the picogram (pg) level . Few other CMPNs were reported for fluorescence‐based sensing of Hg(I), o ‐nitrophenol, nitroanilines, etc . In all the previous examples, the CMPNs were insoluble powders and often used as dispersion in solution or solid state for sensing applications.…”
Section: Cmpn Thin Films For Optical Sensingmentioning
confidence: 99%
“…reported synthesis of CMPNs via olefin metathesis reaction using trifunctional styrene derivatives and studied its fluorescence quenching behavior for the detection of RDX at the picogram (pg) level . Few other CMPNs were reported for fluorescence‐based sensing of Hg(I), o ‐nitrophenol, nitroanilines, etc . In all the previous examples, the CMPNs were insoluble powders and often used as dispersion in solution or solid state for sensing applications.…”
Section: Cmpn Thin Films For Optical Sensingmentioning
confidence: 99%
“…The moderate capacity originated from the low surface area. It was found that nitrogen-rich polymer favored the sorption toward iodine owing to the stronger interaction between nitrogen atom and electron-deficient I2 [4,[32][33]. The inserted images in Figure 4 showed the color change of I2-cyclohexane (1 mg ml -1 ) solution after adding 25 mg of CMOP-1 and CMOP-2.…”
Section: Gas Sorption Capacitymentioning
confidence: 99%
“…NAPOP-1 and NAPOP-3 exhibit high adsorption toward iodine (>240 wt%) and moderate CO2 adsorption [32]. Geng et al constructed novel triazine-based TCMPs by Friedel-Crafts polymerization reaction [33]. Among them, TTPPA displays excellent reversible iodine vapor uptake of 4.90 g g -1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there was attracted considerable attention in the research of novel porous organic polymers (POPs) that have demonstrated great application prospect in iodine capture and fluorescence sensing to iodine and nitroaromatic compounds (NACs) . POPs have developed into a variety of types, including covalent organic frameworks (COFs), polymers of intrinsic microporosity (PIMs), hyper‐cross‐linked polymers (HCPs), covalent triazine‐based frameworks (CTFs), and conjugated microporous polymers (CMPs) …”
Section: Introductionmentioning
confidence: 99%
“…Friedel‐Crafts process catalysis has advantages of high cost‐effectiveness, mild synthetic conditions, good reproducibility, easy treatment, high yield, and high specific surface area . Methanesulfonic acid (CH 3 SO 3 H) and anhydrous aluminum chloride (AlCl 3 ) are commonly used catalysts in Friedel‐Crafts reaction. However, their catalytic effects are affected by the building block structure.…”
Section: Introductionmentioning
confidence: 99%